Supermajordämmerung : the day of the huge integrated international oil company is drawing to a close (2013)
Argues that less reliance by national oil companies on international oil companies, higher fuel efficiencies, stringent fuels standards, the opening up of unconventional natural-gas reserves, development of nuclear power, reduced subsidies for oil use; assistance from service companies; less need to assume the risk of big projects will see the demand for oil falling and the super majors having to diversify.
Keywords: OIL INDUSTRY